2020
DOI: 10.3390/nu12030743
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status in Japanese Adults: Relationship of Serum 25-Hydroxyvitamin D with Simultaneously Measured Dietary Vitamin D Intake and Ultraviolet Ray Exposure

Abstract: Vitamin D insufficiency/deficiency is prevalent worldwide. We investigated the effect of vitamin D intake and ultraviolet ray (UV) exposure on serum vitamin D concentration in Japan. A total of 107 healthy adult participants were recruited from Hokkaido (43 • N) and Kumamoto (33 • N) prefectures. All participants undertook surveys in both summer and winter. Serum 25-hydroxyvitamin D (25(OH)D 3 ) was examined, and vitamin D intake was assessed with a diet history questionnaire. UV exposure was measured with a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 34 publications
0
26
1
Order By: Relevance
“…A total of 24 countries, satisfying the inclusion/exclusion criteria were selected for the analysis ( Table 1 ) [ [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] ]. Study population size varied extensively, from 107 (Japan) to 142,131 (Lebanon).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 24 countries, satisfying the inclusion/exclusion criteria were selected for the analysis ( Table 1 ) [ [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] ]. Study population size varied extensively, from 107 (Japan) to 142,131 (Lebanon).…”
Section: Resultsmentioning
confidence: 99%
“…The Third National Health and Nutrition Examination Survey showed that the dietary intake of vitamin D from food was reported to be lower for female teenagers compared with male teenagers [42]. Furthermore, women tended to avoid tanning, use of sunscreen and sunshade clothing, and this might have caused lower UV exposure energy in women, particularly in summer [10]. In the current study, we speculate that the reasons for the sex differences was boys engaged in greater outdoor physical activity than in girls and girls tended to use sunscreen more than boys.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports of the incidence rate of vitamin D deficiency in Japan. The majority of these reports focus on infants, toddlers [8,9] or adults [10][11][12][13]. There was only one report on adolescent (12-18 years old) vitamin D deficiency in Japan [14].…”
Section: Introductionmentioning
confidence: 99%
“…The Dietary Reference Intake (2020) in Japan determines the Adequate Intake (AI) for vitamin D which was recently reviewed upwards from 5.5 µg/day (220 IU) to 8.5 µg/day (340 IU) ( Table 2 ) [ 69 ]. However, this value is still much lower than in other countries.…”
Section: Guidelines Of Vitamin D Intake and Actual Intakementioning
confidence: 99%